2024
DOI: 10.1186/s12870-024-05170-w
|View full text |Cite
|
Sign up to set email alerts
|

Zinc regulation of chlorophyll fluorescence and carbohydrate metabolism in saline-sodic stressed rice seedlings

Kun Dang,
Jinmeng Mu,
Hao Tian
et al.

Abstract: Saline-sodic stress can limit the absorption of available zinc in rice, subsequently impacting the normal photosynthesis and carbohydrate metabolism of rice plants. To investigate the impact of exogenous zinc application on photosynthesis and carbohydrate metabolism in rice grown in saline-sodic soil, this study simulated saline-sodic stress conditions using two rice varieties, 'Changbai 9' and 'Tonghe 899', as experimental materials. Rice seedlings at 4 weeks of age underwent various treatments including cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Other studies have indicated that an increase in V J is associated with the damage level of PSII donor and acceptor sides under saline-sodic stress 53 . The reduction of ZnO NPs application improves the damage level of PSII donor and acceptor sides, thereby contributing to the increase in PI ABS 54 . Furthermore, the application of ZnO NPs was found to significantly reduce ABS/RC and increase ETo/RC and REo/RC in rice 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that an increase in V J is associated with the damage level of PSII donor and acceptor sides under saline-sodic stress 53 . The reduction of ZnO NPs application improves the damage level of PSII donor and acceptor sides, thereby contributing to the increase in PI ABS 54 . Furthermore, the application of ZnO NPs was found to significantly reduce ABS/RC and increase ETo/RC and REo/RC in rice 55 .…”
Section: Discussionmentioning
confidence: 99%